Floral nectary, nectar production dynamics and chemical composition in five nocturnal Oenothera species (Onagraceae) in relation to floral visitors - Antoń, Sebastian (Planta, 2017)
Main conclusion The floral nectars were sucrose-dominant; however, nectar protein and amino acid contents differed, indicating that composition of nitrogenous compounds may vary considerably even between closely related plant species, irrespectively of nectary structure. Numerous zoophilous plants attract their pollinators by offering floral nectar; an aqueous solution produced by specialized secretory tissues, known as floral nectaries. Although many papers on nectaries and nectar already exist, there has been a little research into the structure of nectaries and/or nectar production and composition in species belonging to the same genus. To redress this imbalance, we sought, in the present paper, to describe the floral nectary, nectar production, and nectar composition in five nocturnal Oenothera species with respect to their floral visitors. The structure of nectaries was similar for all the species investigated, and comprised the epidermis (with nectarostomata), numerous layers of nectary parenchyma, and subsecretory parenchyma. Anthesis for a single flower was short (ca. 10–12 h), and flowers lasted only one night. The release of floral nectar commenced at the bud stage (approx. 4 h before anthesis) and nectar was available to pollinators until petal closure. Nectar concentration was relatively low (ca. 27%) and the nectar was sucrose-dominant, and composed mainly of sucrose, glucose and fructose. The protein content of the nectar was also relatively low (on average, 0.31 µg ml(−1)). Nevertheless, a great variety of amino acids, including both protein and non-protein types, was detected in the nectar profile of the investigated taxa. We noted both diurnal and nocturnal generalist, opportunistic floral insect visitors.